The influence of seed treatment by protectants and microfertilizer on sowing qualities and biological indicators of winter bread wheat - Zaima, O.; Kalitsinska , O. (Quarantine and plant protection, 2025)
Goal. To determine the effect of various protectants and microfertilizer on sowing qualities and biological parameters of winter bread wheat seeds. Methods. There were studied winter bread wheat varieties MIP Valensiia, MIP Vidznaka, MIP Aelita, MIP Fortuna. The influence of the protectants GreenFort Star, Yunta Quattro 373.4 FS, Cruiser 350 FS and their combinations with microfertilizer «5 Element» was investigated. Results. When treating seeds with protectants and their combination with microfertilizer «5 Element» sprouting seed activity increased by 0.3—9.0%, seed vigor by 0.5—6.3%, laboratory germination by 0.3—2.0% compared to the control variants. The higher seed vigor for the varieties MIP Valensiia (96.5%) and MIP Aelita (94.5%) was obtained in variants of treatment by Cruiser 350 FS, MIP Vidznaka (95.8%) by GreenFort Star, MIP Fortuna (96.0%) by Yunta Quattro 373.4 FS. In the varieties MIP Aelita and MIP Fortuna the highest laboratory germination was obtained in the variants of treatment by Cruiser 350 FS and its combination with the microfertilizer, in the varieties MIP Vidznaka and MIP Valensiia by GreenFort Star and its combination with the microfertilizer. In the varieties MIP Aelita and MIP Fortuna the higher field germination was obtained when treating seeds by the preparation Cruiser 350 FS in combination with the microfertilizer «5 Element», while in the varieties MIP Vidznaka and MIP Valensiia by Yunta Quattro 373.4 FS in combination with the preparation «5 Element». Conclusions. It has been determined that treatment of winter bread wheat seeds with preparations under study improved sprouting activity, seed vigor, laboratory and field germination. Preparations of fungicidal and insect-fungicidal action mainly caused shortening of the coleoptile, and the protectant of insecticidal action Cruiser 350 did its lengthening. By complex treatment of seeds by protectants and microfertilizer, more length of coleoptile and the number of primary roots were noted compared with the use of only preparations of protection against diseases and pests. Consequently, the protectants and microfertilizer we studied contributed to the improvement of most of the sowing qualities and biological indicators of the treated seeds.